Cytotaxonomy of the crickets endecous saussure, 1878 with an overview of the chromosomes of phalangopsinae group (Orthoptera: Phalangopsinae) - Zefa, Edison; Fontanetti, Carmem Silvia [UNESP]; De Pinho Martins, Luciano (Magnolia Press, 2010)
The karyotypes of five species of crickets Phalangopsinae were studied: E. onthophagus shows 2n = 19, X0, pairs 1, 7 and 8 metacentric, 2, 3, 6 and 9 submetacentric, 4 and 5 acrocentric; E. itatibensis with 2n = 19, X0, pairs 1, 7 and 8 metacentric, 2, 3, 4, 6 and 9 submetacentric, pair 5 acrocentric; E. cavernicolus with 2n = 21, X0, pairs 7, 8 and 9 metacentric, pairs 1, 2, 3, 4, 5, 6 and 10 acrocentric; E. betariensis with 2n = 21, X0, pairs 2, 4, 8, 9, and 10 submetacentric, 1, 3, 5, 6 and 7 acrocentric; E. alejomesai with 2n = 21, X0, pair 7 metacentric, 1, 2 and 8 submetacentric and 3, 4, 5, 6, 9 and 10 acrocentric. The mechanism of sex determination was X0, XX?, with X chromosome metacentric as the largest of the set. We compared and discussed the karyotypes of the species of Endecouswith an overview of the chromosomes of Phalangopsinae Group. Copyright © 2010 .Magnolia Press.
Keywords: Cytogentics; Ensifera; Grylloidea; Karyotype; Luzarinae